Avizandum statutes on scots property trust and succession law - Steven, Andrew j m
Avizandum Statutes on Scots Property, Trusts and Succession Law contains the main statutory provisions regulating post-feudal land law in Scotland. It covers both heritable and moveable property, as well as trusts and succession law.
Keywords: Real property -- Scotland; Inheritance and succession; Land tenure -- Law and legislation; Trusts and trustees